“EVALUATION OF IMMUNE PARAMETERS AND MODULATORY EFFECTS ON IMMUNE CELLS INDUCED BY NATURAL BIOACTIVE COMPOUNDS DERIVED FROM (CHLORELLA VULGARIS)” (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Humans have long been exploring nature to discover new plant and animal species and to utilize them for economic purposes. Although the development of new plant varieties introduced the concept of "cultivated plants," an entire industry—technical microbiology—emerged, harnessing the activity of bacteria and microscopic fungi to isolate valuable compounds. Until relatively recently, the vast world of microscopic algae, particularly unicellular algae, remained largely unexplored within the scope of human practical activity. When microalgae finally became a focus of study and their potential as unique producers of essential compounds was recognized, Chlorella vulgaris emerged as the most suitable candidate for large-scale cultivation.The identification of antibody-producing cells in the spleen was carried out using the localized hemolysis method on agar, as described by Nordin and Jerne (1963). Toxic hepatitis was used to model secondary immunodeficiency. Rats with toxic hepatitis were administered a 20% solution of CCl₄ (0.2 ml) over three consecutive days and subsequently immunized with erythrocytes, which were injected intraperitoneally.